Discourse on Religious Moderation in Oral Interpretation of the Qur’an on YouTube - Yusufa, Uun; Nabrisah, Zulfan; Pratama, M. Al Qautsar (Institut Agama Islam Negeri (IAIN) Keiri, 2025)
This paper examines the construction of an oral interpretation of the Quran on YouTube channels regarding religious moderation and the power-knowledge relationship that influences it. It is motivated by the reality of religious moderation discourse, as informed by studying the Qur’an and its interpretation. It is shared through social media platforms, such as YouTube, and is used to disseminate various perspectives. By employing a qualitative descriptive method and Michel Foucault’s critical discourse analysis of the oral interpretations of four prominent figures in Indonesian society, this article concludes that the discourse on religious moderation in oral interpretations on YouTube operates within a knowledge power network involving Muslim individuals, countries, media, and communities. The interpretations conveyed by the four figures tend to normalize the understanding of religious moderation as part of the broader teachings of Islam, aligning with the agendas of the government, organizations, and the media. The narrative of religious moderation is constructed through the selection of verses, especially QS al-Baqarah: 143, a textual-contextual combination of interpreting and delivery that emphasizes tolerance and anti-extremism. It is interpreted in the Indonesian context, specifically as religious moderation, characterized by individuals who are tolerant, fair, respectful of one another, and not overly inclined or excessively devoted to their religion. However, the dichotomy between